The importance of incorporating a waste detoxification step in analytical methodologies. Issue 13 (8th June 2015) - Gallart-Mateu, D.; Cervera, M. L.; Armenta, S.; de la Guardia, M.
Abstract : Waste detoxification of copper determination in pesticide formulations improves the green character of the method. In this work: copper was determined in pesticide formulations. Electrogravimetry and atomic spectrometry methods were evaluated from their environmental point of view. The addition of waste decontamination steps improves the greenness of the method. Abstract : The introduction of a waste detoxification step in the analytical process was highlighted using, as example, the determination of copper in pesticide formulations using electrogravimetry, flame atomic absorption spectroscopy and inductively coupled plasma optical emission spectroscopy. This quantitative study showed the improvement of the previously mentioned analytical methods, from a green perspective, after addition of electrodeposition or neutralization steps to the analytical process. Based on this, the application of the eco-scale and the Green Certificate to the evaluation of these methodologies allows the method to be moved from the B and C classes to the A class.